On the Structure of the Units of Group Algebra of Dihedral Group (Communications in Mathematical Research, 2021)
In this paper, we completely determine the structure of the unit group ofthe group algebra of some dihedral groups $D_{2n}$ over the finite field $F_{p^k}$ , where $p$ is aprime.
Keywords: group algebra; unit group; dihedral group.